The role of zeta potential in the adhesion of E. coli to suspended intertidal sediments. (1st October 2018) - Wyness, Adam J.; Paterson, David M.; Defew, Emma C.; Stutter, Marc I.; Avery, Lisa M.
Abstract: The extent of pathogen transport to and within aquatic systems depends heavily on whether the bacterial cells are freely suspended or in association with suspended particles. The surface charge of both bacterial cells and suspended particles affects cell-particle adhesion and subsequent transport and exposure pathways through settling and resuspension cycles. This study investigated the adhesion of Faecal Indicator Organisms (FIOs) to natural suspended intertidal sediments over the salinity gradient encountered at the transition zone from freshwater to marine environments. Phenotypic characteristics of three E. coli strains, and the zeta potential (surface charge) of the E. coli strains and 3 physically different types of intertidal sediments was measured over a salinity gradient from 0 to 5 Practical Salinity Units (PSU). A batch adhesion microcosm experiment was constructed with each combination of E. coli strain, intertidal sediment and 0, 2, 3.5 and 5 PSU. The zeta potential profile of one E. coli strain had a low negative charge and did not change in response to an increase in salinity, and the remaining E. coli strains and the sediments exhibited a more negative charge that decreased with an increase in salinity. Strain type was the most important factor in explaining cell-particle adhesion, however adhesion was also dependant on sediment type and salinity (2, 3.5 PSU > 0, 5 PSU). Contrary to traditional colloidal (Derjaguin, Landau, Vervey, and Overbeek (DLVO)) theory, zeta potential of strain or sediment did not correlate with cell-particle adhesion. E. coli strain characteristics were the defining factor in cell-particle adhesion, implying that diverse strain-specific transport and exposure pathways may exist. Further research applying these findings on a catchment scale is necessary to elucidate these pathways in order to improve accuracy of FIO fate and transport models. Highlights: E. coli zeta potential profiles differ between strains over a salinity gradient. Adhesion efficiency depended on strain > salinity > sediment. Zeta potential did not influence adhesion efficiency. Adhesion to sediments was greatest at moderate salinities tested (2 and 3.5 PSU).